Keuzegids screening & diagnostiek VB - Ulgiati, Aurora Maria; van der Hoek, Marjanne; IJpma, Irene; Dekker, Alain (University of Groningen Press, 2024)
To provide people with intellectual disabilities with appropriate, person-centred care, it is important to properly identify their abilities and limitations. Intellectual disability is characterised by significant limitations in both intellectual and adaptive functioning, arising during the developmental period. But how do you diagnose intellectual disability? And how do you determine its degree? The Keuzegids screening & diagnostiek VB presents a comprehensive overview of Dutch-language instruments to screen or diagnose intellectual and adaptive functioning. Many different instruments are available, but which do you choose? Behaviourists and psychodiagnostics often lack the time and access to the necessary information to make an optimal choice for the individual client. Therefore, Keuzegids screening & diagnostiek VB provides clear overviews of the characteristics of the instruments and the target groups (based on the degree of CB) for which they are suitable. For each target group (developmental delay, LVB, MVB, EV(M)B/ZEVMB), handy selection guides help counsellors and psychodiagnostics choose an instrument that suits their clients. This independent guide is indispensable for behavioural scientists, psychodiagnostic staff and policy makers in intellectual disability care. The book brings together the findings of extensive literature research and prevents every care institution from having to find and compare all the tools all over again. The right methodology for every client?